Alveolar Proteinosis in COVID-19: Clinical Case - Silvia Martin Bote; Maria Angeles Herrera Morueco; Beatriz Arias Arcos; Javier García Lopez; Maria Belen Lopez-Muñiz Ballesteros (Case Reports in Pulmonology)
Pulmonary alveolar proteinosis (PAP) is a rare, diffuse lung disease characterized by accumulation of lipoprotein in lung surfactant in the alveolar space and terminal bronchioles, leading to impaired gas exchange and arterial hypoxemia. We present the case of a 51-year-old woman who was admitted with a diagnosis of severe SARS-CoV-2 pneumonia. Her condition did not improve with corticosteroids. A chest CT scan revealed ground-glass opacities in all lung lobes, with septal thickening. A differential diagnosis was proposed with other diseases. Bronchoscopy revealed milky bronchoalveolar lavage fluid, and staining with periodic acid–Schiff was positive, thus indicating PAP. Therefore, the patient underwent whole lung lavage, which led to clinical, radiological, and functional improvement. In the context of the COVID-19 pandemic, differential diagnosis ensures that appropriate attention is given to less prevalent entities such as PAP.